123 Occupational contact dermatitis: Initial and subsequent workers' compensation claims in Victoria, Australia. (11th October 2013) - Keegel, G; Benke,; Nixon,; Sim,; LaMontagne,
Abstract : Objective: Occupational contact dermatitis (OCD) is caused by a range of workplace exposures such as frequent hand-washing or exposure to irritating or allergic substances. We compare costs and days away from work for initial and subsequent workers' compensation claims for OCD amongst workers in Victoria, Australia. Methods: The Compensation Research Database (CRD), held by the Institute for Safety, Compensation and Recovery Research, contains de-identified details of all workers' compensation claims submitted to the Victorian WorkCover Authority. We accessed injury/disease, employment and demographic variables for OCD claims, as well as information about claim costs (in 2009 Australian dollar equivalent values) and days away from work, for the period January 1985-December 2009. The estimate for the working population denominator is derived from 2001 Australia Bureau of Statistics census data. Results: There were 4773 initial claims and 416 repeat claims for OCD amongst Victorian workers from January 1985- December 2009. The yearly average for initial claims was approximately 9.4 per 100, 000 part-time and full-time working Victorians. The mean cost of repeat claims (7, 556) was higher than the mean cost of initial claims (4, 940). These differences between initial and repeat claims are also reflected in the reported days away from work. The mean days away from work for initial claims was 40 and the mean days away from work for repeat claims was 51. Conclusions: Victorian workers' compensation claims data indicate that the cost and impact of contact dermatitis, as measured by days away from work, increases with repeated workers' compensation claims. Effort needs to be put in place to protect workers from initially developing OCD. For those workers who have developed OCD, a workplace plan needs to be in place for the avoidance or elimination of workplace exposures before the workers return to work.